Sentence Patterns in Motivation Mafia in Instagram: Syntactic Analysis - Rachel Christiara; Ervina CM Simatupang (Budapest International Research and Critics University, 2022)
The research aims to analyze the sentence patterns and describe the categories of phrase found in Motivation Mafia’ motivational quotes. The method used in the research was qualitative method which based on non-numerical elements. This research examined 18 motivational quotes which available online. The data in this research were taken from Motivation Mafia Instagram account. The theories for the research refer to: Greenbaum, S. & Nelson, G. (2002) on sentence patterns and phrase categories theories, Radford (2009) on syntactic categories theory, and Aarts (2001) on syntactic functions theory. The results of the research show that there are 4 sentence patterns: 22% of S+V+C, 50% of (S)+V+O+V+O, 11% of S+V+O+Conj+V+O, and 17% of S+V+A+Conj+S+V+O+V+O. Meanwhile, there are 4 categories of phrase found in motivational quotes: 46 % of noun phrases, 28% of verb phrases, 16% of prepositional phrases, and 10% of adjective phrases.